Hardware-simulator development and implementation for hydraulic turbine generation systems in a district heating system - Jeon, Sung Soo; Lee, Young Jae; Bak, Yeongsu; Lee, Kyo Beum (Electronics (Switzerland), 2020)
This paper presents not only a hardware-simulator development for hydraulic turbine generation systems (HTGS) in a district heating system (DHS) but also its control strategies and sequence. Generally, a DHS uses a differential pressure control valve (DPCV) to supply high-pressure–high-temperature fluids for customers depending on distance. However, long-term exposure of the DPCV to fluids increases the probability of cavitation and leads to heat loss in an event of cavitation. Therefore, a HTGS was introduced to solve this problem. It performs differential pressure control of the fluids, replaces the DPCV, and converts excess energy wasted by the DPCV to electrical energy. In this paper, the development of a hardware-simulator for HTGSs with a back-to-back converter, which uses two-level topologies, is proposed; moreover, control strategies and sequence used in this design are presented. The performance and validity of the proposed hardware-simulator and its control strategies are demonstrated by experimental results.
Keywords: Back-to-back converter; Differential pressure control valve; District heating system; Hardware-simulator; Hydraulic turbine generation system